Language and Culture in Business Translation from English into Arabic - Al Buloshi, Fatemah (2008)
A Master of Arts Thesis in Translation and Interpreting (English / Arabic / English) by Fatemah Al Buloshi Entitled, "Language and Culture in Business Translation from English into Arabic," June 2008. Available are both Hard and Soft Copies of the Thesis.